Effect of Varied Levels of Dietary Crude Protein and Metabolizable Energy on Growth Performance in Giriraja Chicken - Rajwesra, HN; Naikand, Jaya; Nagaraja, CS (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted for 56 days to observe the effect of varied levels of dietary crude protein and metabolizable energy on growth performance in 720 day-old Giriraja chicks, which were divided equally into nine groups of 80 birds each. Nine different experimental diets were formulated with three levels 2700, 2800, and 2900 kcal of metabolizable energy (ME/kg), each with three levels of protein (CP), viz., 19%, 20%, and 21%, respectively and Group T5 served as control fed with 20% protein and 2800 kcal energy as per BIS (2007) requirements. Feed consumption, body weight gain, and feed conversion ratio (FCR) were analysed up to 56 days. The results of the study indicated that diet containing 20% CP with 2900 kcal ME/kg showed enhanced growth performance in Giriraja chicks.
Keywords: Body weight gain; Metabolizable energy; Protein; Giriraja